2020
DOI: 10.1186/s13293-020-00288-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific and shared expression profiles of vulnerability and resilience to trauma in brain and blood

Abstract: Background: While post-traumatic stress disorder (PTSD) is defined by behavioral/cognitive symptoms most directly relevant to brain function, it can be considered a systemic disorder characterized by a distinct inability to reinstate homeostasis after trauma. Methods: In this study, we conducted a secondary analysis of gene expression profiles in key PTSD-relevant tissues, namely blood, amygdala, and hippocampus, from a rat model of PTSD, to identify sex-specific and shared processes associated with individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 98 publications
(111 reference statements)
4
8
0
Order By: Relevance
“…Our work expands upon such results by detailing additional gray matter regions in which oligodendrocytes may influence behavior; specifically, we implicate oligodendrocytes and increased myelin protein histology in the hippocampus and amygdala in anxiety-like phenotypes following stress exposure. In addition, our data support and expand upon a recent study that utilized microarray gene expression data from animals exposed to acute stress, which demonstrated that hippocampal oligodendrocyte proportions are elevated in animals displaying PTSD-like behavioral responses [ 78 ]. Here, we find similar increases in oligodendrocyte density in the hippocampus of animals with high composite anxiety-like behavior scores.…”
Section: Discussionsupporting
confidence: 82%
“…Our work expands upon such results by detailing additional gray matter regions in which oligodendrocytes may influence behavior; specifically, we implicate oligodendrocytes and increased myelin protein histology in the hippocampus and amygdala in anxiety-like phenotypes following stress exposure. In addition, our data support and expand upon a recent study that utilized microarray gene expression data from animals exposed to acute stress, which demonstrated that hippocampal oligodendrocyte proportions are elevated in animals displaying PTSD-like behavioral responses [ 78 ]. Here, we find similar increases in oligodendrocyte density in the hippocampus of animals with high composite anxiety-like behavior scores.…”
Section: Discussionsupporting
confidence: 82%
“…Our work expands upon such results by detailing additional gray matter regions in which oligodendrocytes may influence behavior; specifically, we implicate oligodendrocytes and increased myelin in the hippocampus and amygdala in anxiety-like phenotypes following stress exposure. In addition, our data support and expand upon a recent study that utilized microarray gene expression data from animals exposed to acute stress, which demonstrated that hippocampal oligodendrocyte proportions are elevated in animals displaying PTSD-like behavioral responses (79). Here, we find similar increases in oligodendrocyte density in the hippocampus of animals with high composite anxiety-like behavior scores.…”
Section: Discussionsupporting
confidence: 88%
“…Habituation is, therefore, Sensitization*(-1). From the threshold phase, we averaged startle scores from the 5 presentations of each of the decibel levels (70,80,90,100, and 110 dB) to generate a startle threshold curve for each animal, and we quantified the area under the curve (AUC).…”
Section: Acoustic Startle Response (Asr)mentioning
confidence: 99%
“…However, the study also revealed gender-dependent alterations in several signaling modules (IL-12, MAPK, wound healing, and lipid metabolism), which were associated with specific modes of trauma (Breen et al, 2018). Correspondingly, in a recent PTSD rodent model, researchers detected sex-specific transcriptional responses to trauma involving NF-kB activation (TNF-a upregulation) and dysregulated synaptic plasticity in female HPC (Kim and Uddin, 2020).…”
Section: Sex Influence and Inflammation In Mental Disordersmentioning
confidence: 84%